Design, synthesis, and in silico study of hybrid oxoazetidine conjugated thiazoles as anti‐EGFR with cytotoxicity activity. Issue 4 (29th December 2022) - Pathak, Prateek; Gupta, Santosh; Grishina, Maria; Khalilullah, Habibullah; Verma, Amita
Abstract: We report a series of hybrid oxoazetidine conjugated thiazoles as epidermal growth factor receptor (EGFR) inhibitors, which were synthesized and tested using a variety of in silico and in vitro studies. The compounds were found to be active against breast and hepatic cancer cell lines, with Compounds 7a, 7b, and 7e being the most potent ones. The derivatives were also evaluated for molecular docking and complementarity studies to explicate fundamental substituent groups essential for their bioactivity. Moreover, the structural activity relationship of the analogues was performed for future compound optimization. These studies advocated that the analogues have a high affinity towards EGFR with favorable anticancer potential. The study advised that the derivatives have potency against breast and hepatic cancer and can assist as an initial scaffold for further development of anti‐EGFR compounds.